Финансовые инструменты государственного регулирования экономики: теоретический аспект (Путеводитель предпринимателя, 2020)
Article is devoted the analysis of state regulation of economy by means of tools ofa financial policy. In article necessity of state regulation of economy is proved, the basic directions of the state financial policy and the mechanism of influence of the basicfinancial tools - expenses and incomes of the state budget - on cumulative demand and the cumulative offer in economy are analyzed.